Hubungan Pemberian ASI Eksklusif dengan Kejadian Stunting pada Balita Usia 24-59 Bulan di Desa Sidomulyo Yogyakarta - Martin, Friescha Friecillia; Yekti Satriyandari (CV. CENDIKIA JENIUS INDONESIA, 2024)
Stunting is a condition where growth is disturbed in children, namely that the child's height is lower or shorter (stunted) than the age standard. Based on the results of a preliminary study on May 2 2023, it is known that Sidomulyo Village has the highest percentage of stunting rates at the Godean 1 Community Health Center, namely 13.84% with the lowest prevalence of exclusive breastfeeding coverage, namely 76.66%. This study aims to determine the relationship between exclusive breastfeeding and the incidence of stunting in toddlers aged 24-59 months in Sidomulyo Village, Yogyakarta. This type of research uses a case control design with a retrospective approach. The sampling technique used in this research was a purposive sampling technique, namely 26 samples in the case group and 26 samples in the control group with a ratio of 1:1. Data analysis uses univariate analysis and bivariate analysis. The research was conducted in December 2023. The majority of children aged 24-59 months in Sidomulyo Village, Yogyakarta, were not given exclusive breast milk, 28 respondents (53.8%) while 26 children aged 24-59 months in Sidomulyo Village, Yogyakarta experienced stunting. respondents (50%). The results of statistical tests using chi-square showed a p-value <0.05, which is 0.000 and has a fairly strong correlation with a contingency coefficient value of 0.525. Conclusion : The results of statistical tests show a relationship between exclusive breastfeeding and the incidence of stunting in Sidomulyo Village, Yogyakarta. Recommended The village should work together with the Community Health Center and community cadres to reduce the incidence of stunting.